The Interaction between Gut Microbiota and Pathogenic Bacteria: Implications for Human Health - hashim Taher, Kawthar Mohammed; abdullatif, Amna Akram muhsin; Hamzah, Haneen Fadhil Jaber; Mohsin Alwan, Muntadhar Saleh; Oumaima Basheir Mohammed Hamadi (American Journal of Biology and Natural Sciences, 2024)
The bacteria in the human gut—known collectively as the gut microbiota—play a vital role in promoting health. The ability of beneficial microorganisms in the gut to reduce the ability of harmful microorganisms to colonize the gut and cause disease is one way that they protect us. Understanding these interactions is critical if we are to be able to develop interventions to manage the composition of the microbiota in patients with infections, and potentially with chronic inflammatory conditions. The relationship between the human host and the bacteria that colonize it has long been perceived simply as the non-sterile host environment contesting the colonizing pathogen. Here, we describe an additional layer of interaction between the beneficial microorganisms that normally colonize the gut and the pathogens that can cause life-threatening dysbiosis. We illustrate how the beneficial bacteria can coordinate their response to prevent these detrimental disruptions. We are beginning to probe the benefits of these different activities and gain insight on the potential of bolstering beneficial bacterial activity as an alternative strategy for pathogen management. Over the years, germ theory has led to widespread control of harmful pathogens by chemical means, accompanied by the viewpoint that the majority of bacteria are harmful or of no consequence. However, research into the colonies of microorganisms living in and on humans, namely the human microbiota, has fragmented this view and now we appreciate that the thousands of species of microorganisms residing in our bodies play a crucial role in maintaining our health. When the microbiome becomes unbalanced, and the typical species profile is disrupted, dysbiosis may develop, leading to a potential loss of benefits from the microbiota. Many common pathologies in developed countries, including inflammatory bowel disease, obesity, type 2 diabetes, and atherosclerosis, have been associated with a loss of this microbial balance within the gut. Restoring the balance of the gut microbiota has, in some cases, been shown to ameliorate the resultant disease, but significant challenges remain that will need to be overcome if we are to exploit our beneficial gut bacteria in this way.